2013
DOI: 10.5897/ajpp12.620
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some micronutrients and Citharexylum quadrangular extract against liver fibrosis in Schistosoma mansoni infected mice

Abstract: Despite effective chemotherapy, schistosomiasis remains the second major public health problem in the developing world, second to malaria. The present study was undertaken to explore the therapeutic effect of the micronutrients (vitamin E and selenium) and chloroform extract of Citharexylum quadrangular leaves and their mixture against the deleterious pathological impacts induced in mice livers by Schistosoma mansoni infection. Parasitological markers showed that oral ingestion of the different supplements to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 74 publications
8
14
0
Order By: Relevance
“…Necrosis or membrane damage releases the enzymes into circulation; therefore, they can be measured in the serum. In agreement with the reports of Kadry et al (2013) and Mahmoud and Elbessoumy (2013), the increment of such enzymes in serum may be due to the destruction of hepatocytes by the action of toxins of the parasite eggs leading to their release into the circulation. In addition, Naik et al (2011) reported that hepatocyte membrane damage seems to be the prime culprit for the marked increase in the serum marker enzymes, AST, ALT, and ALP following schistosomal (2011), data from the present study showed that treatment with Mef at the two tested doses for juvenile and adult stages significantly decreased the levels of serum AST, ALT, ALP and GGT activities in infected-treated group indicating maintenance of functional integrity of hepatic cell membrane.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Necrosis or membrane damage releases the enzymes into circulation; therefore, they can be measured in the serum. In agreement with the reports of Kadry et al (2013) and Mahmoud and Elbessoumy (2013), the increment of such enzymes in serum may be due to the destruction of hepatocytes by the action of toxins of the parasite eggs leading to their release into the circulation. In addition, Naik et al (2011) reported that hepatocyte membrane damage seems to be the prime culprit for the marked increase in the serum marker enzymes, AST, ALT, and ALP following schistosomal (2011), data from the present study showed that treatment with Mef at the two tested doses for juvenile and adult stages significantly decreased the levels of serum AST, ALT, ALP and GGT activities in infected-treated group indicating maintenance of functional integrity of hepatic cell membrane.…”
Section: Discussionsupporting
confidence: 86%
“…Schistosomiasis is a prevalent parasitic disease in tropical and sub-tropical areas, which accounts for the second place in terms of socioeconomic and public health burden (Cardoso et al, 2013;Kadry et al, 2013). Each year schistosomiasis afflicts up to 600 million people in 74 tropical and sub-tropical countries, predominantly in the developing world (El Ridi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the study made by Shalaby and Bahgat (2003), who reported stronger antimicrobial activity against Gram negative bacteria and positive bacteria tested by disc diffusion method. Different species of the genus Citharexylum were reported to have antiulcer, antihypertensive and hepatoprotective effects, immunomodulatory, antimicrobial, anti-Schistosoma mansoni activities, antioxidant nephroprotective, radical scavenging, cytotoxic activities and regulating immediate type of allergic reaction (Shin et al, 2000;Khalifa et al, 2002;Shalaby and Bahgat, 2003;Bahgat et al, 2005;Khan and Siddique, 2012;Kadry et al, 2013;Allam, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Genus Citharexylum was reported to contain triterpenes, sterols, irridoids, lignan glycoside, phenolic and flavonoids. Different species of genus Citharexylum are famous to have antiulcer, antihypertensive, hepatoprotective effects, immunomodulatory, antimicrobial, anti-Schistosomal, antioxidant, nephroprotective, radical scavenging, cytotoxic activities and regulating immediate type of allergic reaction (Khalifa et al, 2002;Ganapaty et al, 2010;Khan and Siddique, 2012;Kadry et al, 2013; *Corresponding author. E-mail: kh.omran@yahoo.com.…”
Section: Introductionmentioning
confidence: 99%
“…The mice were inoculated intraperitoneally with Plasmodium berghei and baseline was established as published by Ekpo and Ekanemesang (2016) and Kadry et al (2013).…”
Section: Inoculationmentioning
confidence: 99%